AUDIO MIXER 4 CHANNELS STEREO - Mochammad Karjadi; Bambang Harianto; Kunto Wibowo (International Journal Science and Technology, 2023)
In audio equipment, the mixer is a tool that is well known and widely used by lovers of stereo 4-channel audio mixers such as those used in recording studios, transmitter stations and so on, all of which function to mix several signals, in a ratio that can be adjusted with a potentio meter. In the world of electronics signals can be mixed by summing them. In this research discusses the performance of the simplest 4-channel stereo channel audio mixer system consisting of two channels and can be developed up to dozens of channels. Four channels as a microphone amplifier and two channels (L and R) for channels that can be connected to tape, tuner, compact disc and others, as well as two output channels 1 (L and R) and output channel 2 (R and L) that can be connected to a power amplifier.